2012
DOI: 10.1055/s-0032-1323783
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Sodium Valproate in Patients Suffering from Bipolar Disorders: Comparing Acute and Maintenance Phases of Mania

Abstract: No significant effect of the acute phase of mania was observed in bipolar patients and no relationship could be found between drug pharmacokinetics and disease phase. This may be explained by specific pharmacokinetic features of the drug such as low extraction ratio values. However, phase by gender interactions indicate possible gender-related issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Nowadays, SV is one of the preferred options in the treatment of BPD. Kamalinia et al [14] showed that neither the trough concentration nor the internal clearances of SV in the acute phase of mania differed statistically or descriptively from those in the maintenance phase.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, SV is one of the preferred options in the treatment of BPD. Kamalinia et al [14] showed that neither the trough concentration nor the internal clearances of SV in the acute phase of mania differed statistically or descriptively from those in the maintenance phase.…”
Section: Introductionmentioning
confidence: 99%
“…O Valproato é quase totalmente metabolizado pelo mecanismo de primeira passagem e é considerado um substrato menor de CYP2A6, 2B6, 2C9, 2C19 e 2E1 90,91 . O desdobramento metabólico do ácido valpróico é bem complexo e resulta na produção de, ao menos, 14 metabólitos diferentes 92 . As reações de conjugação correspondem por cerca de 50% do metabolismo, outros 40% são em decorrência da beta-oxidação realizada pelas mitocôndrias nas células do fígado, gerando metabólitos 92,93 .…”
Section: Metabolizaçãounclassified
“…Os principais metabólitos formados na beta-oxidação do ácido valpróico incluem 3-oxo-VPA, Δ2(E) -VPA e 3-hydroxy-VPA. Na via metabólica do retículo endoplasmático incluem produtos hidroxilados pelo metabolismo do citocromo P450 (5-OH-VPA, 3-OH-VPA e 4-OH-VPA), cetonas em decorrência da oxidação de 4-OH-VPA ou 3-OH-VPA, e ácidos dicarboxilícos decorrentes da oxidação de 5-OH-VPA e 4-OH-VPA (ácido propylglutarico, Figura 1 -Estrutura química do Ácido Valpróico ácido propylsuccinico) 92 . Alguns desses metabólitos são ativos.…”
Section: Metabolizaçãounclassified